Local Self-Governance and Varieties of Statehood Tensions and Cooperation - Neubert, Dieter; Lauth, Hans-Joachim.; Mohamad-Klotzbach, Christoph (Cham : Springer International Publishing : Imprint: Springer, 2022)
The debate on governance originates in the OECD world. At the latest since the postcolonial debate, we know that we need to "test" our assumptions under radically different conditions. This book offers an extended perspective of local self-governance by examining cases from South Asia, Africa, and Latin America, together with a study of militias in the USA. The chapters present a wide variety of local actors who pursue different notions of order legitimized by local traditions based on hierarchy or deeply rooted communalism, Islamic theology, or grassroots democracy. Some local actors claim a state-like authority and challenge the territorial state. In such cases, there is no longer "a shadow hierarchy" but opposition to the state. Different violent actors fight for supremacy, and the state is just one actor among others. The empirical studies presented in this book show how different kinds of local self-governance are combined with varieties of statehood, and thus contribute to an understanding of the notion of governance in a fundamental sense that goes beyond the special case of the OECD world.
Local Self-Governance and varieties of statehood: Reflections on tensions and cooperation -- U.S. Domestic Militias' Intersections with Government and Authority: How a sociology of individualism informs their praxis -- Paradoxes of local self-governance: Legitimation strategies of rural councillors under national and global influences in Africa -- Enacting the housing crises through self-organization? The Cissie Gool occupation of Reclaim the City and its ambivalent relationship to the Capetonian municipality (South Africa) -- What is "local" and what is "self" in local self-help organisations, and can they work effectively? Experiences from the grass-roots level in Bolivia -- Pathalgadi Movement, Self-governance, and the Question of 'Weak State-hood' -- Samaj as a Form of Self-Organisation among Village Communities in the Chittagong Hill Tracts, Bangladesh -- Jihadi governance in northern Mali: Socio-political orders in contest -- Cyrenaica Contemporary: Politics, Identity, and Justice in Times of Transition -- Local Self-governance and Varieties of Statehood: Some Remarks from an Ancient Historian.
Keywords: Comparative government; Political science; Urban policy; Asia-Politics and government; America-Politics and government; Africa-Politics and government; Comparative Politics; Governance and Government; Urban Policy; Asian Politics; American Politics; African Politics